Recent trends in the synthesis of graphene and graphene oxide based nanomaterials for removal of heavy metals — A review - Lim, Jihn Yih; Mubarak, N. M.; Abdullah, E. C.; Nizamuddin, Sabzoi; Khalid, Mohammad *; Inamuddin, (Elsevier, 2018)
The advanced synthesis and development of raw graphene based on various significant functionalization has been outstanding in the wastewater treatment compared to the other alternatives such as carbon nanotubes and other carbon nanomaterials. Nano size graphene is known to possess large surface area and some promising properties in terms of mechanical, electrical, chemical and magnetism. Besides, the graphene can be generated via both Top-down and Bottom-up methods such as chemical exfoliation, chemical vapour deposition and other techniques so that it can be further functionalized to form graphene oxide-based nanomaterials. Hence, graphene oxide-based nanomaterials are discovered to be useful in the application of heavy metal removal from wastewater. In short, this paper critically reviewed on the synthesis method of graphene and application of graphene oxide-based nanomaterials in the term of heavy metal removal. The advantages, drawbacks, comparison of the data efficiencies, and research requirements are further highlighted, elaborated and discussed detailly. Lastly, the future challenges of graphene are elaborated. Therefore, it can be guaranteed that the wastewater discharged should be detected with the minimum or none of the heavy metals so that minimum effects on the ecosystem is discovered.